The seeds of invasion: enhanced germination in invasive European populations of black locust (Robinia pseudoacacia L.) compared to native American populations - Bouteiller, X P; Moret, F; Ségura, R; Klisz, M; Martinik, A; Monty, A; Pino, J; van Loo, M; Wojda, T; Porté, A J; Mariette, S (Plant biology (Stuttgart, Germany), 2021)
Local adaptation and the evolution of phenotypic plasticity may facilitate biological invasions. Both processes can enhance germination and seedling recruitment, which are crucial life-history traits for plants. The rate, timing and speed of germination have recently been documented as playing a major role during the invasion process. Black locust (Robinia pseudoacacia L.) is a North American tree, which has spread widely throughout Europe. A recent study demonstrated that a few populations are the source of European black locust. Thus, invasive populations can be compared to native ones in order to identify genetic-based phenotypic differentiation and the role of phenotypic plasticity can thereby be assessed. A quantitative genetics experiment was performed to evaluate 13 juvenile traits of both native and invasive black locust populations (3000 seeds, 20 populations) subjected to three different thermal treatments (18 °C, 22 °C and 31 °C). The results revealed European populations to have a higher germination rate than the native American populations (88% versus 60%), and even when genetic distance between populations was considered. Moreover, this trait showed lower plasticity to temperature in the invasive range than in the native one. Conversely, other studied traits showed high plasticity to temperature, but they responded in a similar way to temperature increase: the warmer the temperature, the higher the growth rate or germination traits values. The demonstrated genetic differentiation between native and invasive populations testifies to a shift between ranges for the maximum germination percentage. This pattern could be due to human-mediated introduction of black locust.
Keywords: stromy; life-history traits; American Indian or Alaska Native; Germination; seedlings; phenotypic plasticity; lidé; Robinia; Robinia pseudoacacia; genetic differentiation; klíčení; Seeds; indián nebo domorodec z Aljašky; Humans; black locust; semena rostlinná; biological invasion; quantitative genetics; germination; Trees